Interventional EUS for the Diagnosis and Treatment of Locally Advanced Pancreatic Cancer - Al-Haddad, Mohammad; Eloubeidi, Mohamad A (JOP. Journal of the Pancreas, 2016)
Endoscopic ultrasound (EUS) evolved as the diagnostic test of choice evaluating suspected pancreatic tumors. Coupled with fine needle aspiration (FNA), EUS provides high accuracy for the diagnosis and staging of pancreatic cancer. Novel EUS based techniques have emerged as a safe minimally invasive alternative to the surgical or radiological approaches. By allowing better pain control, delivering antitumor therapies or draining obstructed bile ducts, such techniques hold a big promise to improve the quality of life of patients with unresectable pancreatic cancer. In this review, we will discuss the role EUS-FNA plays in the diagnosis, staging and treatment of patients with locally advanced pancreatic cancer. Image: EUS-guided fiducial placement in a patient with locally advanced pancreatic cancer.